ANALISIS PENGARUH INOVASI PRODUK, BRAND DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN DI KAOS GAPLEK KEDIRI - RAMADHAN, MUHAMMAD MASAAUR (Universitas Nusantara PGRI Kediri, 2022)
This study aims to analyze the effect of Product, Brand and Digital Marketing Innovation on Purchase Decisions. This research was conducted in Kaos Gaplek Kediri. Purchase Decision is the dependent variable in this study, while Product Innovation, Brand and Digital Marketing are independent variables. Questionnaire data were obtained from consumers of T-shirts Gaplek Kediri. The number of samples in this study was 58 people. The analytical technique used in this study is multiple linear regression with a 5% confidence level to obtain a comprehensive picture of the relationship between one variable and another. The results showed that the variables of Product Innovation, Brand and Digital Marketing partially had a significant effect on Purchase Decisions. Based on the results of the F test, it is known that the Product Innovation, Brand and Digital Marketing variables simultaneously have a significant effect on Purchase Decisions. The adjusted R Square results show a value of 0.790 or 79% which means that the magnitude of the influence of Product, Brand and Digital Marketing Innovation on Purchase Decisions together (simultaneously) is 79%, while the remaining 21% is explained by other factors that are not investigated in this study.